57th International Astronautical Congress 2006
DOI: 10.2514/6.iac-06-d4.2.05
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of the Track of the Space Elevator

Abstract: A string moving with geostationary angular velocity in its radial relative equilibrium configuration around the Earth, reaching from the surface of the Earth far beyond the geostationary height, could be used as track for an Earth to space elevator. This is an old dream of mankind, originating about 100 years ago in Russia. Besides the question of feasibility from a technological point of view also the question concerning the stability of such a configuration has not yet been completely solved. Under the assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The characteristic of the curves in Fig. 3 are the same that we gained from the continuous string model [2]. Although the current model cannot evaluate different materials, the fact that for a given stiffness a limited reachable altitude for the inner mass exists is very interesting and is also true for the continuous model.…”
Section: Elastic Dumb-bellmentioning
confidence: 78%
See 2 more Smart Citations
“…The characteristic of the curves in Fig. 3 are the same that we gained from the continuous string model [2]. Although the current model cannot evaluate different materials, the fact that for a given stiffness a limited reachable altitude for the inner mass exists is very interesting and is also true for the continuous model.…”
Section: Elastic Dumb-bellmentioning
confidence: 78%
“…3 are shifted to the right. In a more sophisticated model [2] the mass of the rods is also taken into account and is therefore adequate to decide which material can be used in a Space Elevator. The characteristic of the curves in Fig.…”
Section: Elastic Dumb-bellmentioning
confidence: 99%
See 1 more Smart Citation
“…Pugno [187] studied the strength of carbon nanotube-based space elevator cable and concluded that the actual strength of the cable would be reduced by ~70% of theoretical estimation due to presence of defects. Pugno et al [188] studied the stability of the track of space elevator and concluded that the track in itself is orbitally unstable, but attaching an adequately heavy satellite can stabilize it. CNTs are also used in aircraft wiring [189], propulsion [190], lightening protection [191] and stealth aircraft designs [192].…”
Section: Applicationsmentioning
confidence: 99%